UV radiation simultaneously affects phototrophy and phagotrophy in nanoflagellate-dominated phytoplankton from an Andean shallow lake - Bastidas Navarro, Marcela Alejandra (2011)
Mixotrophic nanoflagellates, that combine photosynthesis and phagotrophy, are important members of planktonic food webs in many aquatic environments depending on the balance among the different carbon and energy sources.  We carried out field sampling and laboratory experiments with natural nanoflagellate assemblages from an Andean North-Patagonian lake exposing them or not to UVR, measuring photosynthetic parameters and bacterivory. The effect of different light treatments on the photosynthetic efficiency was studied by the non-invasive, pulse amplitude modulated (PAM) fluorescence technique, and bacterivory was assessed with fluorescently labeled bacteria (FLB). Mixotrophic nanoflagellates were clearly dominant (up to 90% of total phytoplankton and 88% of total nanoflagellate abundance), and in the experiments, labeled bacteria were observed in more than 75% of mixotrophic cells. These results support the idea that these phytoflagellates were never entirely photosynthetic. The high light: phosphorus ratio and the high C:N:P ratio suggest a strong nutrient limitation towards P. Our results show that both functions, photosynthesis and bacteria ingestion, were simultaneously reduced by UVR. We estimated that UVR exposure reduced the photosynthetic parameters around 31% while ingestion rates around 29%. Therefore, our results stresses that the different cell functions could be concurrently impacted by UVR implying that C transfer would be substantially altered in the microbial food web.